Sejarah Perkembangan GKPS Pertama Dikota Medan Tahun 1952 - Nasution, Muhammad Ihsan Syahaf; Sipayung, Dahlia V H; Pasaribu, Erich Panissah; Br Gurusinga, Elia Dwi Septania; Siahaan, Melisa N (Innovative: Journal Of Social Science Research, 2024)
The birth of GKPS started from evangelism in the land of Simalungun which was relatively slow, because after several years since evangelism entered the land of Simalungun, no one has given himself to be baptized. Finally Jalung Wismar Saragih (1888-1968) was baptized on September 11, 1910. J. Wismar also became the first pastor of the land of Simalungun The slow development of the Gospel in the land of Simalungun was caused because the preaching of the gospel was not carried out using the Simalungun language, but the Toba language, therefore formerly the simalugun tribal congregation still joined the HKBP. The development of Islam that has influenced the Simalungun people has also become another factor inhibiting the gospel in the land of Simalungun. In addition, another factor is the lack of attention of the zendelings to the people in Simalungun. The lack of attention of the HKBP and Batakmission gave rise to the initiative of the Simalungun people to secede from the HKBP. Aritonang and Steenbrink note that in 1928, a desire to bathe itself arose already. In 1935, the HKBP gave a special district to the people of Simalungun and appointed Rev. J. Wismar Saragih to lead the district. The district was later named HKBPS (Simalungun Protestant Batak Christian Huria). Cultural and linguistic differences further strengthened the simalungun people's intention to bathe themselves from the HKBP. Finally on September 1, 1963, HKBPS changed its name to GKPS